THE DIGITAL PROVIDE: INFORMATION (TECHNOLOGY), MARKET PERFORMANCE AND WELFARE IN THE SOUTH INDIAN FISHERIES SECTOR - Robert Jensen (THE QUARTERLY JOURNAL OF ECONOMICS Vol. CXXII August 2007 Issue 3, 2007)
When information is limited or costly, agents are unable to engage in optimal arbitrage. Excess price dispersion across markets can arise and goods may not be allocated efficiently; in this setting, information technologies may improve market performance and increase welfare. Between 1997 and 2001, mobile phone service was introduced throughout Kerala, a state in India with a large fishing industry. Using micro-level survey data, we show that the adoption of mobile phones by fishermen and wholesalers was associated with a dramatic reduction in price dispersion, the complete elimination of waste and near-perfect adherence to the Law of One Price. Both consumer and producer welfare increased